Dylematy etyczne rozwoju sportu zawodowego - Pawlak, Zbigniew; Smoleń, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2010)
This paper discusses in detail the ethical issues in the contemporary professional sports and shows how these issues are addressed in the European Union countries and in the United States. From the ethical perspective it was decided that it is disputable to finance companies in competitive sports from a public purse (central and local government purse), to sponsor football clubs by bookmaking companies, to pay compensations (financial equivalents) for the change of membership in clubs by the players (the so called transfers). It was noticed that in the era of deepening sports commercialisation and application of ambush marketing strategies a real problem has become how to protect the interests of sport fans. It was decided that reaching of a certain scale of business operations (e.g. a certain threshold of revenues or profits) by monopolistic sports organisations should be paralleled by their loss of privileged status and/or change of their organisational and legal status (change from voluntary, non-profit organisations into companies operating under commercial law).